Pembuatan Minuman Herbal Jahe dan Serai sebagai Upaya Meningkatkan Kesadaran Hidup Sehat di Desa Sei Simujur: Penelitian - Lesiana; Rani Anggraini; M.Arifin Ilham; Widya Sari; Dea Laila; Hidayat (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Health is an essential aspect of community life that can be supported through the habit of consuming herbal drinks. Ginger (Zingiber officinale) and lemongrass (Cymbopogon citratus) are two traditional plants widely used as herbal beverages due to their diverse health benefits, including boosting the immune system, improving blood circulation, and aiding detoxification. This article describes the implementation of a community service program in Sei Simujur Village that focused on the production of ginger–lemongrass herbal drinks as an effort to promote healthy living and foster creative economic opportunities. The program was carried out through lectures, demonstrations, hands-on practice, group discussions, and evaluations using pre-test and post-test questionnaires. A total of 30 participants, consisting of housewives, youth, and village officials, were involved. The pre-test results showed that only 35% of participants had adequate knowledge about the benefits of ginger and lemongrass, while the post-test revealed a significant increase to 93%, indicating a 78% improvement. Furthermore, participants successfully practiced the preparation of herbal drinks independently with correct composition and hygienic techniques. From an economic perspective, a simple simulation showed that the production cost of one 100 ml bottle was approximately Rp2,500, while the selling price ranged from Rp5,000 to Rp6,000. This margin of profit demonstrates the potential for developing ginger–lemongrass herbal drinks as a micro-enterprise in rural communities. Challenges encountered include product shelf-life limitations and lack of flavor variations, which can be addressed through natural preservation methods and diversification of ingredients. In conclusion, this program effectively enhanced community awareness of healthy living, empowered local skills, and inspired the development of value-added herbal products